PEMBIASAAN BUDAYA SEKOLAH MELALUI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI MADRASAH IBTIDAIYAH NIDHOMUT THOLIBIN KABUPATEN LAMONGAN - Nur Hamidah; Muhammad Hanief; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
Although the subject of Religion has been taught in Madrasas, it seems that is still does not work. This can be seen starting from small things that have become the habits of students such as the habits of students who like to cheat on their friends during tests, the behavior of students who like to fight against the teacher when in the learning process in class, likes to bully friends when studying, annoy friends. when studying in class, the lack of courtesy of students. These cases often occur in schools, especially in this Madrasa. Teachers' efforts to cultivate good personalities for students can be done by implementing the values of Islamic Religious Education that have been taught through habituation activities both in religious activities and daily activities at school. This study aims to describe and analyze strategies for inculcating school culture through Islamic religious education at Madrasah Ibtidiyah Nidhomut Tholibin. This research approach uses a qualitative case study type. The learning process of Islamic religious education is carried out by implementing the values that have been taught which are integrated through the cultivation of school culture. So that the results of this study can be used as an example in planning and implementing school culture planting based on Islamic religious education learning at Madrasah Ibtidaiyah. Kata Kunci: Penanaman, Budaya Sekolah, Pembelajaran PAI